التخطيط البيئي المحلي في التشريع الجزائري - ريحاني, أمينة (revue mofakir, 2018)
Rethinking the new style of environmental protection in the form of permits to understand their concerns through the development of a variety of mechanisms administrative appear in the style of planning and tracking phases of the evolution of the sector to the specialist environmental, on the basis that the task of caring for the environment a local issue administratively a regional rather than a central issue, but the modern style planning local and lack of goals each upbringing Touselh found his need to develop an effective strategy to improve the defects for the purposes of access to the local environmental development. Is it contributed to the local environmental planning taken by the Algerian legislature to ensure the protection of the environment . ?